Best Answer

3x3=9

So, it could only be 9x1 which=9.

3x1=3

3 does not equal 9.

4x2=8

8 does not equal 9.

6x3=18

18 does not equal 9

Study guides

☆☆

Q: What is equal to the product of 3X3 9X1 3X1 4X2 6X3?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

4X2+X3+3X+7Y+2X3 can only be simplified to 3X3+4X2+3X+7Y, because X3 and 2X3 are the only like terms.

X=3 y=2 (3x3) + (4x2) = 17 9 + 8 = 17

There aren't two numbers that match your criteria. 6+0=6 6x0=0 5+1=6 5x1=5 4+2=6 4x2=8 3+3=6 3x3=9

ANSWER: -4X2 -8X-4x (x+2)= (-4x * x) + (-4x*2)= -4X2 -8X

It is 4x2 + 426x + 630.

Related questions

Given 3x3 + 4x2 +x + 7 is divided by x2 + 1, find the results:

72 ^ 9x8 ^ ^ 3x3 4x2 ^ 2x2

4X2+X3+3X+7Y+2X3 can only be simplified to 3X3+4X2+3X+7Y, because X3 and 2X3 are the only like terms.

3/4 x 1/2 = 3x1 / 4x2 = 3/8

If you mean '2x4' as in 2 times 4- 2x4= 8 3x3= 9 4x2= 8 8-9-8=-19 if you want to divide by x -b/c x doesn't have a set amount- it would be: -19/x

8

X=3 y=2 (3x3) + (4x2) = 17 9 + 8 = 17

11

(x3 + 4x2 - 3x - 12)/(x2 - 3) = x + 4(multiply x2 - 3 by x, and subtract the product from the dividend)1. x(x2 - 3) = x3 - 3x = x3 + 0x2 - 3x2. (x3 + 4x2 - 3x - 12) - (x3 + 0x2 - 3x) = x3 + 4x2 - 3x - 12 - x3 + 3x = 4x2 - 12(multiply x2 - 3 by 4, and subtract the product from 4x2 - 12)1. 4x(x - 3) = 4x2 - 12 = 4x2 - 122. (4x2 - 12) - (4x2 - 12) = 4x2 - 12 - 4x2 + 12 = 0(remainder)

There aren't two numbers that match your criteria. 6+0=6 6x0=0 5+1=6 5x1=5 4+2=6 4x2=8 3+3=6 3x3=9

ANSWER: -4X2 -8X-4x (x+2)= (-4x * x) + (-4x*2)= -4X2 -8X

not necessarily. take the example of a 3x3 square and a 4x2 rectangle. Both have a perimeter of 12. but the square has an area of 9 and the rectangle has an area of 8.